2020
DOI: 10.3389/fvets.2020.559279
|View full text |Cite
|
Sign up to set email alerts
|

A Fixed Cohort Field Study of Gene Expression in Circulating Leukocytes From Dairy Cows With and Without Mastitis

Abstract: Specifically designed gene expression studies can be used to prioritize candidate genes and identify novel biomarkers affecting resilience against mastitis and other diseases in dairy cattle. The primary goal of this study was to assess whether specific peripheral leukocyte genes expressed differentially in a previous study of dairy cattle with postpartum disease, also would be expressed differentially in peripheral leukocytes from a diverse set of different dairy cattle with moderate to severe clinical mastit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…These differences in leukocyte profiles between calves and mature cattle are also the likely reason that three of our genes of interest ( LIF , IFNG , and TNF) had consistently low copy numbers in our samples and were unable to be reliably included in DGE analysis. Although these genes are well documented inflammatory mediators in older cattle [ 14 , 17 , 29 , 30 ], they are evidently not prolifically expressed by peripheral leukocytes of young calves.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These differences in leukocyte profiles between calves and mature cattle are also the likely reason that three of our genes of interest ( LIF , IFNG , and TNF) had consistently low copy numbers in our samples and were unable to be reliably included in DGE analysis. Although these genes are well documented inflammatory mediators in older cattle [ 14 , 17 , 29 , 30 ], they are evidently not prolifically expressed by peripheral leukocytes of young calves.…”
Section: Discussionmentioning
confidence: 99%
“…Genes were prioritized that have strong evidence for their role in amplification or attenuation of inflammatory processes, the antibacterial or antiviral actions of their protein products, or their involvement in disease resistance and tolerance mechanisms. Five internal control genes ( ACTB , GOLGA5 , OSBPL2 , SMUG1 , and YWHAZ ) were also selected based on their previously demonstrated suitability as controls in bovine peripheral leukocytes [ 29 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bovine mastitis, caused by a variety of organisms, including Staphylococci, Streptococci, and Enterobacteria, is a mammary gland infection posing a great threat to the dairy industry, and is the costliest disease affecting cattle, due to its impact on the quality and quantity of milk production 1 , 2 . The immune response to pathogens in the mammary gland is highly complex, having to first identify the pathogen, recruit the appropriate immune cells, remove the pathogen, and then terminate the inflammatory response 3 . Recent studies have shown that mammary epithelial cells (MEC) initiate this process by changing the expression of various genes which are responsible for a wide range of immunological and inflammatory responses 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Bovine mastitis, caused by a variety of organisms, including Staphylococci, Streptococci, and Enterobacteria, is a mammary gland infection posing a great threat to the dairy industry, and is the costliest disease affecting cattle, due to its impact on the quality and quantity of milk production 1,2 . The immune response to pathogens in the mammary gland is highly complex, having to rst identify the pathogen, recruit the appropriate immune cells, remove the pathogen, and then terminate the in ammatory response 3 . Recent studies have shown that mammary epithelial cells (MEC) initiate this process by changing the expression of various genes, responsible for a wide range of immunological and in ammatory responses 4 .…”
Section: Introductionmentioning
confidence: 99%